Reputation in a dark network of online criminals. - Décary-Hétu, David; Dupont, Benoit (Global Crime, 2013)
This paper focuses on criminals who could easily be labelled as entrepreneurs and who deal in compromised computer systems. Known as botmasters, these individuals use their technical skills to take over and control personal, business and governmental computers. These networks of hijacked computers are known as botnets in the security industry. With this massive computing power, these criminals can send large amounts of spam, attack web servers or steal financial data – all for a fee. As entrepreneurs, the botmasters' main goal is to achieve the highest level of success possible. In their case, this achievement can be measured in the illegitimate revenues they earn from the leasing of their botnet. Based on the evidence gathered in literature on legitimate and illegitimate markets, this paper sets to understand how reputation could relate to criminal achievement as well as what factors impact a heightened level of reputation in a criminal market.